Population genomics resolves cryptic species of the ecologically flexible genus Laspinema (Cyanobacteria) - Dvořák, Petr; Skoupý, Svatopluk; Jarošová, Hana; Páleníčková, Kateřina; Stanojković, Aleksandar (Journal of phycology, 2024)
Cyanobacterial taxonomy is entering the genomic era, but only a few taxonomic studies have employed population genomics, which provides a framework and a multitude of tools to understand species boundaries. Phylogenomic and population genomic analyses previously suggested that several cryptic lineages emerged within the genus Laspinema. Here, we apply population genomics to define boundaries between these lineages and propose two new cryptic species, Laspinema olomoucense and L. palackyanum. Moreover, we sampled soil and puddles across Central Europe and sequenced the 16S rRNA gene and 16S-23S ITS region of the isolated Laspinema strains. Together with database mining of 16S rRNA gene sequences, we determined that the genus Laspinema has a cosmopolitan distribution and inhabits a wide variety of habitats, including freshwater, saline water, mangroves, soil crusts, soils, puddles, and the human body.
Keywords: Soil Microbiology; sinice; fylogeneze; gene flow; cryptic species; phylogenomics; Cyanobacteria; new species; sekvenční analýza DNA; RNA ribozomální 16S; evolution; Phylogeny; RNA, Ribosomal, 16S; DNA bakterií; DNA, Bacterial; population genomics; Sequence Analysis, DNA; půdní mikrobiologie; cyanobacteria